A Biomechanical Assessment of Direct and Inertial Head Loading in Rugby Union - TIERNEY, GREGORY JOHN (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2018)
Rugby union is a territorial, dynamic and high-impact collision sport. Unfortunately, due to its physical and high impact nature, the incidence of concussion is high. There is mounting evidence that repeatedly sustaining concussion injuries can lead to long-term brain health issues. Furthermore, the adverse effects of repeated sub-concussive impacts in contact sport are an emerging concept. Despite this, little research has been conducted on the regular head loading environment associated with rugby union. In particular, the magnitude and influencing factors associated with direct head impacts and inertial head loading are poorly understood. Accordingly, the aim of this thesis is to biomechanically assess direct and inertial head loading in rugby union to identify prevention strategies. The thesis is split into two main areas: direct head impacts and inertial head loading. A combination of general video analysis, 3D motion analysis, multibody modelling and a novel approach known as Model-Based Image Matching (MBIM) was utilised. For direct head impacts, an initial aim was to understand how head impacts were occurring in rugby union. A general video analysis review of elite level competitions discovered that the tackle accounted for 60% of direct head impacts. The tackler was much more likely to receive a direct head impact than the ball carrier. Additional video analysis identified tackle characteristics that have a lower propensity to result in a tackler Head Injury Assessment (HIA) and a positive influence on tackle success. Specific tackler proficiency variables were identified such as identify/track ball carrier onto shoulder, head up and forward/face up, shortening steps and head placement on correct side of ball carrier. For the ball carrier, much fewer tackle characteristics were identified, however incorrect fending was identified as a risk factor for upper body front-on tackles. A large majority (81%) of tackle related direct head impacts occurred in the second half of games. A disproportionate number of direct head impacts from upper body tackles (63%) occurred in the final quarter. However, tackling proficiency was found to remain relatively constant throughout the game. Instead, more tackles occur in the final quarter of a game. Further video analysis identified that tackling at the upper trunk accounted for nearly half (47%) of all tackler HIAs and had no greater propensity to result in tackler success outcomes. Tackling at the upper trunk and upper legs had a greater propensity to result in a tackler HIA. MBIM is a novel approach for measuring six degree of freedom head kinematics from uncalibrated multiple camera view video footage of sporting head impacts. An assessment was conducted on the accuracy of the MBIM method. A vehicle-cadaver head-windscreen impact case was utilised. Reflective marker-based motion capture system head kinematic time-histories were available as an independent measure. The method exhibited Root Mean Square Errors (RMSE) between 10-20 mm for linear displacement and 0.01-0.03 rad for rotational displacement for reconstructing 6 degree of freedom head motion. However, the MBIM method was deemed unsuitable for measuring componential angular velocity during direct head impacts (RMSE up to 5.61 rad/s). For inertial head loading, MBIM was utilised to measure the head kinematics of a visually unaware ball carrier during an active shoulder tackle to the upper trunk. The componential head angular velocities were similar to the average values previously reported for concussive direct head impacts. This is a potentially concern. It was postulated that lower tackle heights may reduce inertial head kinematics for the ball carrier. Staged tackles in a motion analysis laboratory and multibody modelling simulations indicated that higher tackle heights cause greater ball carrier inertial head kinematics. By tackling below the upper trunk, the multibody simulations suggest that average ball carrier peak head linear acceleration, angular acceleration and change in angular velocity values could be reduced in the tackle by 35%, 61% and 40%, respectively. Based on the staged tackles, median ball carrier peak head linear acceleration, angular acceleration and change in angular velocity values could be reduced in the tackle by 44%, 55% and 57%, respectively. The MADYMO ellipsoid human body model was assessed for reconstructing head kinematics during the abovementioned staged tackles. The results indicated that the model is currently unsuitable for detailed reconstruction of head kinematics on an individual case basis. However, the model identified the kinematic trend that upper trunk tackles cause greater ball carrier inertial head kinematics than mid/lower trunk tackles, even with significant variations in initial player-to-player configurations and speeds. The findings from this thesis provide an evidence base, at the elite level, for coaches to develop and implement technical based concussion prevention strategies. Focus should be placed on safe and proficient tackle technique. Upper trunk tackles were identified as a risk factor for direct head impacts for tacklers and high inertial head kinematics for ball carriers. Tackling at the upper trunk of the ball carrier should be discouraged. Instead, coaching strategies should place emphasis on tackling at lower HIA risk body regions such as the mid and lower trunk.
APPROVED
Keywords: Concussion; Sport